2017
DOI: 10.1242/jcs.192104
|View full text |Cite
|
Sign up to set email alerts
|

CD4 downregulation by the HIV-1 protein Nef reveals distinct roles for the γ1 and γ2 subunits of the AP-1 complex in protein trafficking

Abstract: The HIV accessory protein Nef is a major determinant of viral pathogenesis that facilitates viral particle release, prevents viral antigen presentation and increases infectivity of new virus particles. These functions of Nef involve its ability to remove specific host proteins from the surface of infected cells, including the CD4 receptor. Nef binds to the adaptor protein 2 (AP-2) and CD4 in clathrin-coated pits, forcing CD4 internalization and its subsequent targeting to lysosomes. Herein, we report that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 83 publications
6
36
0
Order By: Relevance
“…The depletion of the AP-11A subunit of AP-1, known to be present in both AP-1␥1and AP-1␥2-containing variants of AP-1 (29), led to the codepletion of AP-1␥1 and AP-1␥2, as previously observed (26). This treatment resulted in the full recovery of HLA-A surface levels in cells expressing Nef (Fig.…”
Section: Fig 2 Ap-1␥2supporting
confidence: 67%
See 2 more Smart Citations
“…The depletion of the AP-11A subunit of AP-1, known to be present in both AP-1␥1and AP-1␥2-containing variants of AP-1 (29), led to the codepletion of AP-1␥1 and AP-1␥2, as previously observed (26). This treatment resulted in the full recovery of HLA-A surface levels in cells expressing Nef (Fig.…”
Section: Fig 2 Ap-1␥2supporting
confidence: 67%
“…Several studies using RNA interference demonstrated that the expression of both 1A and ␥1 subunits is required for the downregulation of MHC-I by Nef (12)(13)(14)(15)23). Interestingly, there is growing evidence that some of these isoforms may combine to form functionally distinct AP-1 complexes (24)(25)(26)(27)(28). Indeed, we have previously demonstrated that a functional variant of AP-1 that contains ␥2 (AP-1␥2), but not the AP-1␥1 complex, is required for efficient downregulation of CD4 by Nef (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were seeded on 13-mm-diameter coverslips and fixed at the indicated times p.i. and processed for Immunofluorescence assay as previously described [ 54 ]. For dsRNA detection, using J2 antibody, samples were processed according to [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our Y2H screen also identified various proteins involved in protein processing, including the endogenous γ2 isoform of AP-1 (AP1G2), which has been shown to interact with both MOPV and LASV Z protein. Interestingly, a previous study demonstrated that the HIV-1 protein Nef interacts with AP1G2 in clathrin-coated pits to promote efficient internalization of its co-receptor CD4 and its subsequent targeting to lysosomes, therefore counteracting the detrimental effects of high CD4 expression in HIV-infected cells, such as to prevent superinfection [52]. It is possible that this protein plays a similar role during MOPV or LASV infection, by promoting internalization of the alpha-dystroglycan, which acts as a reservoir for these viruses, to facilitate viral entry steps or limit the cell infection and subsequent over-stimulation of innate immune responses.…”
Section: Discussionmentioning
confidence: 99%